Law Enforcement of Traffic Violations Using Electronic Traffic Law Enforcement (E-TLE) Based on Law No. 22 Of 2009 on Road Traffic and Transportation (In The Jurisdiction of Karawang Regency) - Novia Sucita; Rr. Dijan Widijowati; Edi Saputra Hasibuan (Journal of Social Research, 2025)
The primary objective of this research is to analyze the implementation of E-TLE in Karawang Regency, identify the challenges encountered, and propose solutions to improve its effectiveness in reducing traffic violations and enhancing road user discipline. This study evaluates the implementation of Electronic Traffic Law Enforcement (E-TLE) in Karawang Regency, focusing on the obstacles and solutions in enforcing traffic regulations. E-TLE is an electronic-based law enforcement tool aimed at improving driving discipline and reducing extortion during traffic violation enforcement. The research uses a normative method, analyzing secondary data to draw conclusions about the impact of E-TLE on reducing traffic violations and improving community compliance. The challenges identified include the high costs of required infrastructure, non-compliance by some road users, and a tendency for better orderliness only when police officers are physically present. The study suggests that the Police should collaborate with local governments to provide necessary infrastructure, increase public awareness through socialization efforts, and continue to deploy officers at strategic locations to ensure enforcement effectiveness.